Quito, Cuenca y Guayaquil en 1840: un estudio demográfico comparativo (Estudios) - Hamerly, Michael T. (2022)
The present article examines and compares the socioeconomic features of Ecuador’s three largest cities in 1840 by retrieving the first population census conducted that year. The research explores the outcomes of contemporary population surveys, certificates of baptism/birth, marriage, and burial/death in Quito and Guayaquil. As for Cuenca, parish records are also included. The article suggests there is a huge volume of data on the demographic status and mobility of Ecuador’s population in the nineteenth century that still needs to be retrieved.